SOBRE ORATORIA ESCRITA - López Eire, Antonio (Myrtia, 2001)
Hellenistic and Later Greek Rhetoric differ from that of the Classical Period in several ways. Although the practice of declamation remained vigorous in the schools, a new kind of Oratory was born in Athens, in the IVth century B.C., that reflects the central position of Rhetoric in education. It was a written, moral and epideictic Oratory based on Isocratean principles. As is well known, this orator, Isocrates, opened a school, abandoned judicial speech, wrote speeches and insisted upon moral conciousness growing out of the process of rhetorical education and composition. This kind of scholar, moral and philanthropical rhetoric, with its written speeches, was continued later, as can be seen in several speeches of Aelius Aristides and Libanius.